16-year WRF simulation for the Southern Alps of New Zealand - Kropac, Elena; Mölg, Thomas; Cullen, Nicolas James (2023)
The climatological dataset was produced using the Weather and Research Forecasting (WRF) model, version 4.2.2, configured with two nested domains at 10 km (D1) and 2 km (D2) horizontal grid spacing. It covers most of the South Island of New Zealand and is centered over Brewster Glacier in the Southern Alps. The model was forced every three hours by ERA5 reanalysis data at its outer lateral boundaries. The dataset spans the period of 1 January 2005 to 31 December 2020, providing daily output in the outer domain (D1) and 3-hourly output in the innermost domain (D2). The data provided here are a selection of daily averages from the inner WRF domain (D2; 2-km grid spacing). They are distributed among three different file types containing 4-dimensional, 3-dimensional and time-invariant output variables, respectively. For the 4-dimensional fields, perturbation and base-state atmospheric pressure (WRF variables P and PB) and geopotential (PH and PHB) were combined to produce full model fields (PRES and GEOPT). Perturbation potential temperature (T) was converted to total potential temperature (THETA). Wind vectors (U,V, and W) were converted to mass points and rotated to earth coordinates.<br